Universities as anchor institutions in place-based development: Implications for South African universities engagement - Fongwa, S. (South African Journal of Higher Education, 2023)
The concept of anchor institutions has emerged as a more integrated way in which universities are engaging with their communities towards achieving social and economic transformation of the city regions as well as the university itself. Starting in the United States, the anchor institution concept has widely gained currency, especially for universities in historically disadvantaged or socio-economically declining communities. Exacerbated by Covid-19, many universities are reviewing their place-based mandates within a period where communities are facing huge and increasing socio-economic demise. This article teases out the core components of an anchor university to argue for a more active hands-on and outcome-oriented approach to university-community engagement for South African universities. The article identifies facets for anchoring including economic transformation, infrastructural development, and sociocultural transformation. Four active functions for universities are proposed within their immediate communities. These include a core institutional role, an economic role, an infrastructure development role, and a public good role. The last section provides a reflection on possible pathways for South African universities to adopt an anchoring posture and mandate.